Feeding preferences and population parameters of sergestid shrimps, Acetes japonicus kishinouye in the coastal waters of Kedah, Malaysia - Abdulaziz A, Alsayed Amani (2011)
Food and feeding habits, diet composition and population parameters of Acetes japonicus in the estuarine waters of Tanjung Dawai, Kedah Peninsular Malaysia were studied between June 2008 and May 2009. The total catches of Set Bag Net (SBN)were constituted of three major fauna groups and they were Acetes shrimps (89%), juvenile fishes (9%) and non- Acetes shrimps (2%). The annual mean percentage composition of sergestid shrimp comprising of A. japonicus, A. vulgaris and A. indicus were 89%, 7% and 4% espectively. Although seven species of juvenile fishes were recorded together in the bag net from the study area, the abundance was however very low (9%). Feeding habits of sergestid shrimps A. japonicus were done by examining the stomach contents of 164 specimens during one year study period. Analysis on the percentage of numerical abundance (Ci) showed that plant matter (28.18%) and crustacean appendages (18.70%) as the two highest values amongst the eight categories of feeding items. In addition, percentage frequency of occurrence (Fpi) values of phytoplankton, zooplankton, algae, plant matter, appendages of crustacean, debris, unidentified items and sand-mud were 3.45%, 7.05%, 5.07%, 27.44%, 17.42%, 15.80%, 8.94% and 19.81% espectively. From the diet composition found in the stomach, it is revealed that A. japonicus is probably omnivorous in feeding habit. Population parameters of male and female A. japonicus were studied using the monthly length frequency data by FiSAT software to evaluate the mortality rates and its exploitation level. The sex ratio (males: females) was found to be 1: 0.94. Asymptotic length (L∞) was 25.20 mm and 28.88 mm for male and female respectively. Growth co-efficient (K) for males and females was estimated at 1.80 yr-1 and 1.30 yr-1 respectively. Total mortality (Z) was calculated at 5.98 yr-1and 4.44 yr-1 for male and female of A. japonicus correspondingly. Natural mortality (M) was 2.82 yr-1 and 2.19 yr-1 for male and female shrimps. While fishing mortality (F) was 3.16 yr-1 and 2.25 yr-1 for male and female respectively. Exploitation level (E) for male and female of A. japonicus was calculated at 0.53 and 0.51. The exploitation level was slightly over (E > 0.50) the optimum level of exploitation (P = 0.50). The stock of A.japonicus was found to be slightly over exploited in Tanjung Dawai coastal waters.